Rapid synthesis: Supporting population-health management to meet the needs of patients and community partners in rural and mixed urban-rural environments - Dion, A; Waddell, K; Moat, KA; Lavis, JN (My University, 2021)
An in-depth synthesis of what is known based on the best available global research evidence (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about population-health management to meet the needs of patients and community partners in rural and mixed urban-rural environments in response to a decision-makers’ request.
Keywords: population-health; management; needs; patients; community partners; rural; urban-rural